Peptide‐Drug Conjugate for Therapeutic Reprogramming of Tumor‐Associated Macrophages in Breast Cancer - Anni Lepland; Elisa Peranzoni; Uku Haljasorg; Eliana K. Asciutto; Maria Crespí‐Amer; Lorenzo Modesti; Kalle Kilk; Manuel Lombardia; Gerardo Acosta; Miriam Royo; Pärt Peterson; Ilaria Marigo; et al. (Advanced Science)
Abstract In triple‐negative breast cancer (TNBC), pro‐tumoral macrophages promote metastasis and suppress the immune response. To target these cells, a previously identified CD206 (mannose receptor)‐binding peptide, mUNO was engineered to enhance its affinity and proteolytic stability. The new rationally designed peptide, MACTIDE, includes a trypsin inhibitor loop, from the Sunflower Trypsin Inhibitor‐I. Binding studies to recombinant CD206 revealed a 15‐fold lower KD for MACTIDE compared to parental mUNO. Mass spectrometry further demonstrated a 5‐fold increase in MACTIDE's half‐life in tumor lysates compared to mUNO. Homing studies in TNBC‐bearing mice shows that fluorescein (FAM)‐MACTIDE precisely targeted CD206+ tumor‐associated macrophages (TAM) upon intravenous, intraperitoneal, and even oral administration, with minimal liver accumulation. MACTIDE was conjugated to Verteporfin, an FDA‐approved photosensitizer and YAP/TAZ pathway inhibitor to create the conjugate MACTIDE‐V. In the orthotopic 4T1 TNBC mouse model, non‐irradiated MACTIDE‐V‐treated mice exhibited anti‐tumoral effects comparable to those treated with irradiated MACTIDE‐V, with fewer signs of toxicity, prompting further investigation into the laser‐independent activity of the conjugate. In vitro studies using bone marrow‐derived mouse macrophages showed that MACTIDE‐V excluded YAP from the nucleus, increased phagocytic activity, and upregulated several genes associated with cytotoxic anti‐tumoral macrophages. In mouse models of TNBC, MACTIDE‐V slowed primary tumor growth, suppressed lung metastases, and increased markers of phagocytosis and antigen presentation in TAM and monocytes, increasing the tumor infiltration of several lymphocyte subsets. MACTIDE‐V is proposed as a promising peptide‐drug conjugate for modulating macrophage function in breast cancer immunotherapy.